PERAN PEMERINTAH DALAM MEMINIMALISIR EKSPLOITASI ANAK - Fajarwati (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2026)
Child exploitation is a form of human rights violation that remains a social problem in Indonesia. The government has the primary responsibility to protect children from all forms of exploitation through policy, law enforcement, education, and community empowerment. This study discusses the government's role in minimizing child exploitation. The results demonstrate the government's strategic role in minimizing child exploitation through regulation, supervision, education, family economic empowerment, and victim rehabilitation. Literature research indicates that the success of child protection is highly dependent on cross-sector collaboration and consistent policy implementation at all levels of government.